A Critical Evaluation of the Effectiveness of Performance Appraisal Methods - wang, ye (2017)
This study evaluates the effectiveness of several performance appraisal methods in a critical way and compares them from different perspectives to illustrate the benefits as well as limitations of each of them. Further it also identifies how the participants think about these methods in practice in order to verify the arguments form academics. The objective of this dissertation is to make people have a better understanding of the features of different performance appraisal methods, and help them to adopt these techniques in an effective way. The study followed exploratory approach where researches about these performance appraisal methods are provided with practical evidences collected from a group of interviewees. Besides, this study was depended on qualitative technique for collecting data where the interviews were used to collect the data from 12 employees in four different companies, among which two of the companies are from the UK while the other are from China.